Efecto in vitro de extractos de bokashi sobre el nematodo fitófago Meloidogyne hapla - Rodríguez, Andrea Susana; Azpilicueta, Claudia Viviana; Nico, Andrés Ignacio; Barrionuevo, Myriam Elisabeth (Asociación Argentina de Fitopatólogos (AAF), 2025)
Poster y resumen